Маркери стресу та центральна гемодинамiка при пiсляоперацiйному знеболеннi у новонароджених - Курочкін, Михайло Юрійович; Чемерис, Ю. О.; Курочкин, М. Ю.; Чемерис, Ю. А.; Kurochkin, M. Yu.; Chemerys, Yu. A. (Полтава: УМСА, 2015)
Проведено вивчення особливостей деяких маркерів стресу, центральної гемодинаміки у новонароджених в післяопераційному періоді. Дослiдження проведено у 41 новонародженого, 22 з них з метою пiсляоперацiйного знеболення отримували фентанiл, а 19 дiтей- центральні нейроаксіальні блокади, якi виконувались шляхом одноразового каудально- епідурального введення місцевого анестетика (0,2 % бупівакаїна або наропіна) в об’ємі 1 мл/кг 1-2 рази на добу, протягом 2-3-х діб. Комбінована анестезія у новонароджених в післяопераційному періоді з використанням одноразових каудальних блокад має кращий аналгетичний ефект, ніж традиційне знеболення наркотичними анальгетиками, що підтверджено достовірним зниженням рівня кортизолу і відсутністю достовірних коливань рівнів iнсулiну і глюкози в крові. Проведено изучение особенностей некоторых маркеров стресса, центральной гемодинамики у новорожденных в послеоперационном периоде. Исследования проведены у 41 новорожденного, 22 из них с целью послеоперационного обезболивания получали фентанил, а 19 детей – центральне нейроаксиальные анестезии, которые выполнялись путем однократного каудально- эпидурального введения местного анестетика (0,2 % бупивакаина или наропина) в объеме 1 мл/кг 1-2 раза в сутки в течение 2-3-х суток. Комбинированная анестезия у новорожденных в послеоперационном периоде с использованием одноразовых каудальных блокад имеет лучший анальгетический эффект, чем традиционное обезболивание наркотическими анальгетиками, что подтверждено достоверным снижением уровня кортизола и отсутствием достоверных колебаний уровней инсулина и глюкозы в крови. Postoperative pain remains an urgent problem in the XXI century – both in our country and abroad. According to the literature, from pain syndrome affected from 30 to 75 % of patients in the postoperative period. The main objective of all anesthesiologists is to eliminate pain, regardless of its causes. For quality analgesia in surgical neonates, mostly abroad, widely used-caudal epidural combined with general anesthesia. The aim of research – to study the characteristics of some markers of stress, central hemodynamics in infants with surgical pathology in the postoperative period when combined anesthesia using central neuroa x ial blockade. Materials and methods. The study of hemodynamics, levels of glucose, cortisol and insulin conducted in 41 newborn with surgical pathology (esophageal atresia, atresia of the rectum, high and low intestinal obstruction, etc.). For the 1 group, included 19 children, was used neuroa x ial central blockade in the postoperative period which were performed by a single caudal epidural-introduction of local anesthetic (bupivacaine 0.2 % or naropinå) 1 ml / kg 1-2 times per day for 2-3 days. The second group consisted of 22 children and with the aim of anesthesia, fentanyl was carried out continuous infusion at the dose of 5 mcg / kg / min for 2-3 days. Children of 1 group also received a similar dose of fentanyl, but after 1 day moved on considerably less dose – 1-3 mg / kg / h, further analgesia was performed using paracetamol in age doses. Results. Hemodynamic parameters at the first stage og research in children of two groups were characterized as moderate hyperdynamia of circulation – cardiac inde x (CI) -4,65- 4.7 L / min / m 2 , heart rate (HR) of 160 beats / min; stroke inde x (MI) posted as indicators of middle-age; Arterial pressure (MAP) was 51.2 and 45.6 mm, respectively, and CVP was slightly lower and amounted to 15 mm. H2O.; Cortisol levels in the blood of newborns of the first group was 321,72 ± 48,70 mkmol/l, in children of the second group- 355,63 ± 46,39 mkmol / l, insulin levels averaged 49 MKOD / ml and glucose – 4.5 mmol / l. At the second stage of the study there was a significant decrease in cortisol by 25.5 % in children who received anesthesia with fentanól and by 84.2 % in the blood of children who underwent central neura x ial blockade, was also observed nonsignificant decrease in insulin levels by 7.5 % in children of the first group, and significant decrease of 21 % in the second group of infants. There wasn’t significant fluctuations of the level of glucose at all stages of the study in the blood of newborns from the 1 group, but here was reliable increase glucose level in the second step was 47.3 % compared to the previous stage in the second group. There were insignificantly decrease of CI and HR – 9 % in children of the first group and by 6 % in infants of the second group. Characteristically sustainable recovery of intestinal peristalsis, lack of sewage by gastric tube in children of the main group, adequate hourly urine output of 3-4 ml / kg / h. The third phase showed complete normalization of hemodynamic, significant decrease in markers of stress in patients of the second group. No change (growth)of markers of stress in children from the study group and at the same time reliable increase glucose levels and reduced insulin levels in children in the control group (2) show the benefits of a stress analgesia combined caudal anesthesia in postoperative analgesia in newborn infants before anesthesia using opioids (fentanyl). Conclusion. Combined anesthesia in infants in the postoperative period with using a single caudal blockade has better analgesic effect than traditional pain relief narcotic analgesics, which confirmed a significant decrease cortisol levels and absence of significant fluctuations of insulin levels and blood glucose. Using of caudal anesthesia in infants with congenital malformations of the gastrointestinal tract in postoperative period favors a stable hemodynamics, can significantly reduce the doses of narcotic analgesics to reduce the term children on mechanical ventilation and restore motor – evacuation function of the intestine to 24 hours of postoperative period.
Маркеры стресса и центральная гемодинамика при послеоперационном обезболивании у новорожденных
Markers of Stress and Central Hemodynamics in Postoperative Analgesia in Newborns
Keywords: новонароджені; хірургічна патологія; каудальна анестезія; гемодинаміка; кортизол; інсулін; глюкоза; новорожденные; хирургическая патология; каудальная анестезия; гемодинамика; кортизол; инсулин; глюкоза; Neonate; Surgical Pathology; Caudal; Anesthesia; Hemodynamics; Cortisol; Insulin; Glucose